Extreme thermal environments: reservoirs of industrially important thermozymes - Pandey, Anita; Dhakar, Kusum (Frontiers in Microbiology, 2026)
Extreme thermal environments, both natural (e.g., hot springs, fumaroles, geysers, mud pots, deep-sea hydrothermal vents) and man-made (e.g., compost heaps, sawdust, coal refuse piles), are rich sources of thermophilic microorganisms, including Bacteria and Archaea. These organisms possess unique adaptations that allow survival and metabolic activity at elevated temperatures, making them valuable sources of thermostable and thermoactive enzymes. This review synthesizes current knowledge on thermophiles, including their phylogeny, adaptation mechanisms, and cultivation strategies. We discuss the industrial applications of thermozymes, such as DNA polymerases and other thermostable enzymes, and highlight the role of genomics, systems biology, and bioinformatics in accelerating enzyme discovery. The review also addresses the astrobiological relevance of thermophiles as models for life in extreme extraterrestrial environments and emphasizes the importance of conservation and sustainable use of natural thermal habitats. Collectively, this overview provides a comprehensive perspective on the ecological, biotechnological, and fundamental research significance of thermophiles and their enzymes.